Soil Classification Using Horizontal to Vertical Spectrum Ratio Methods on Scilab in Sendangmulyo, Semarang - Prima Vitra Varecha; Andi Fadllan; Hartono Hartono (Physics Education Research Journal, 2022)
Microtremor is ambient vibration on the surface ground by natural phenomena, human activities, etc. Microtremor data can be processed using various software such as Geopsy, easyHVSR, and MATLAB. Another alternative software to process microtremor data is Scilab. This research was conducted to classify the soil using HVSR methods on Scilab 6.1.0. in Sendangmulyo, Semarang. Data processing includes generating synthetic signals, coding the HVSR methods on Scilab, synthetic data testing, processing microtremor data, and mapping of natural frequency () and predominant period (). Coding tests are performed against synthetic signals and can display a pre-set .  from the HVSR spectrum then processed to get the . The  in Sendangmulyo, Semarang ranged from 1.280 Hz – 18.504 Hz, and the  ranged from 0.054 s – 0,781 s. Based on the  and , Sendangmulyo is composed of hard soil, medium soil, soft soil, and very soft soil.